State of Road and Transport Networks in Sikkim - Singha, Komol; Rajesh Raj, S. N. (Arthshastra Indian Journal of Economics & Research, 2020)
Transportation infrastructure is one of the important factors for the growth and development of an economy. In the Himalayan region like Sikkim, a good quality road network can help in reducing isolation and economic vulnerability as it is the only mode of transport in the region. Using primary and secondary data, this paper analyzed the inter - district and inter â€“ organizational performance of the road networks in Sikkim. By employing the principal component analysis technique, we found that the East Sikkim district outperformed the other districts in the state. Of the four indices employed, the â€œsystem condition and preservation,â€ which includes six physical components of road quality, turned out to be the best. Though the road density was not found to be very high, the average physical condition of the roads available in the state turned out to be quite impressive. However, the inter-district variation, in terms of vehicle density, was found to be quite high, concentrated mainly in the capital city.